2017
DOI: 10.4236/health.2017.911111
|View full text |Cite
|
Sign up to set email alerts
|

Effective of Behavioral Treatment Combined with Psychological Counseling for Female Coital Disorder of Chinese

Abstract: Objective: To explore the effects of the behavioral treatment combined with psychological counseling on female coital disorder in China. Methods: One hundred and sixteen female patients with coital disorder were divided into sexual behavior training combined with psychological counseling group (group A, 59 cases) and psychological counseling alone group (group B, 57 cases). Results: Forty-five cases cured (76.27%), eight eases improved (13.56%), and six cases invalid (10.17%), the general rate of effectiveness… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…Finally, after reading the full text, we found that 8 articles were not RCTs, and the outcomes of the 3 studies were not what we wanted. The remaining 92 studies [10–101] all contained all or part of the outcomes that we needed, so they were included in this study. The review process is illustrated in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, after reading the full text, we found that 8 articles were not RCTs, and the outcomes of the 3 studies were not what we wanted. The remaining 92 studies [10–101] all contained all or part of the outcomes that we needed, so they were included in this study. The review process is illustrated in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…High school students' academic pressure is heavy, and they are in the second accelerated period of physical development. Many behaviors in daily life need to consume self-control resources, so that their words and deeds can contribute to their long-term interests and meet the expectations of important others [3]. As an important talent reserve group in China, contemporary high school students live in an increasingly superior environment and experience fewer twists and turns and setbacks, which means that the psychological resilience of high school students is weakening [4].…”
Section: Introductionmentioning
confidence: 99%